Eccrine Porocarcinoma of Scalp: a Rare Case Report - pal, Subrata (Iran J Pathol, 2015)
Eccrine porocarcinoma is a rare malignant adnexal tumor of ductal portion of eccrine sweat gland. It occurs commonly in the lower extremities and rarely in scalp, face, ear, trunk and upper extremities. This survey presents a classic case of eccrine porocarcinoma of scalp in a 58 yr old male patient, presenting as cauliflower like growth over parietal aspect of scalp.